An evaluation of the COVID-19 recommendation map identified diverging clinical and public health guidance - Nasir, Zil H; Mertz, Dominik; Nieuwlaat, Robby; Santesso, Nancy; Lotfi, Tamara; Motilall, Ashley; Moja, Lorenzo; Mbuagbaw, Lawrence; Klugar, Miloslav; Turgeon, Alexis F; Mathew, Joseph L; Canelo-Aybar, Carlos; et al. (Journal of clinical epidemiology, 2022)
OBJECTIVES: To describe divergence between actionable statements issued by coronavirus disease 2019 (COVID-19) guideline developers cataloged on the "COVID-19 Recommendations and Gateway to Contextualization" platform. STUDY DESIGN AND SETTING: We defined divergence as at least two comparable actionable statements with different explicit judgments of strength, direction, or subgroup consideration of the population or intervention. We applied a content analysis to compare guideline development methods for a sample of diverging statements and to evaluate factors associated with divergence. RESULTS: Of the 138 guidelines evaluated, 85 (62%) contained at least one statement that diverged from another guideline. We identified 223 diverging statements in these 85 guidelines. We grouped statements into 66 clusters. Each cluster addressed the same population, intervention, and comparator group or just similar interventions. Clinical practice statements were more likely to diverge in an explicit judgment of strength or direction compared to public health statements. Statements were more likely to diverge in strength than direction. The date of publication, used evidence, interpretation of evidence, and contextualization considerations were associated with divergence. CONCLUSION: More than half of the assessed guidelines issued at least one diverging statement. This study helps in understanding the types of differences between guidelines issuing comparable statements and factors associated with their divergence.
Keywords: COVID-19; Public Health; Humans; veřejné zdravotnictví; lidé